Some Aspects of Improving the Management System of Enterprises of the Baking Industry in Ukraine - Ostrovetskyy, V. (Економічний вісник Донбасу, 2021)
The article deals with certain issues of improving the management system of the enterprises of the baking industry in Ukraine. It is noted that the baking industry is an important strategic component of the Ukrainian food industry. Problems arising in this industry have a negative impact on the food security of Ukraine, as well as worsen macroeconomic dynamics, stimulating inflation. It is substantiated that the key element in ensuring the sustainable development of the enterprises of the baking industry in Ukraine is the calculation of the cost of manufactured products. Costing allows to monitor and track deviations of actual indicators from those that were taken into account in the planning process of the production period. It is advisable to organize monitoring of changes in the components of the sale price of bread and bakery products and its comparison with price dynamics in commodity markets in the Direct-Costing-System management accounting system, which is gaining popularity due to the expansion of the use of international financial reporting standards. У статті розглядаються окремі питання щодо вдосконалення системи управління підприємствами хлібопекарської галузі України. Зазначається, що хлібопекарська галузь є важливою стратегічною складовою харчової промисловості України. Проблеми, що виникають у цій галузі, негативно впливають на продовольчу безпеку України, а також погіршують макроекономічну динаміку, стимулюючи інфляцію. Обґрунтовується, що ключовим елементом забезпечення сталого розвитку підприємств хлібопекарської галузі України є калькулювання собівартості продукції. Калькуляція дозволяє здійснювати моніторинг та відслідковувати відхилення фактичних показників від тих, що були враховані у процесі планування виробничого періоду. Організацію моніторингу зміни складових ціни реалізації хліба та хлібобулочних виробів та її порівняння з ціновою динамікою на сировинних ринках доцільно здійснювати у системі управлінського обліку Direct-Costing-System, яка набирає популярності у зв'язку з розширенням застосування міжнародних стандартів фінансової звітності. В статье рассматриваются отдельные вопросы совершенствования системы управления предприятиями хлебопекарной отрасли Украины. Отмечается, что хлебопекарная отрасль является важной стратегической составляющей пищевой промышленности Украины. Проблемы, возникающие в этой отрасли, негативно влияют на продовольственную безопасность Украины, а также ухудшают макроэкономическую динамику, стимулируя инфляцию. Обосновывается, что ключевым элементом обеспечения устойчивого развития предприятий хлебопекарной отрасли Украины есть калькулирование себестоимости выпускаемой продукции. Калькуляция позволяет осуществлять мониторинг и отслеживать отклонения фактических показателей от тех, которые были учтены в процессе планирования производственного периода. Организацию мониторинга изменения составляющих цены реализации хлеба и хлебобулочных изделий и ее сравнения с ценовой динамикой на сырьевых рынках целесообразно осуществлять в системе управленческого учета Direct-Costing-System, которая набирает популярность в связи с расширением применения международных стандартов финансовой отчетности.